O nível da taxa básica de juros e o spread bancário no Brasil: Uma análise de dados em painel - Félix António Manhiça; Caroline Teixeira Jorge (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This study aims to analyze the impact of macroeconomic variables, especially the prime rate of the economy, on the interest margin (spread) charged by Brazilian banks from 2000 to 2010. To achieve this goal, the study adopted the behavior model of the banking firm developed by Ho and Saunders (1981), as well as, an econometric method, the system-GMM, based on panel data from 140 commercial banks. The objective was to test whether the loan spread, after corrected through idiosyncratic differences between the banks, reacted to macroeconomic risk factors. Through empirical analysis focused on macroeconomic variables it was concluded that the spread responds to the level of the benchmark interest rates. Within the macroeconomic variables, the unemployment rate and the risk measured by the EMBI were also important in determining the loan spread. The volatility of interest rates, however, showed no significant results.
Keywords: F13; 330; Zinsspanne; Zinsstruktur; Volatilität; Zins; Brasilien